Antarctic Bottom Water Sensitivity to Spatio‐Temporal Variations in Antarctic Meltwater Fluxes - Wilton Aguiar; Sang‐Ki Lee; Hosmay Lopez; Shenfu Dong; Hélène Seroussi; Dani C. Jones; Adele K. Morrison (Geophysical Research Letters, 2023)
Abstract Ice sheet melting into the Southern Ocean can change the formation and properties of the Antarctic Bottom Water (AABW). Ocean models often mimic ice sheet melting by adding freshwater fluxes in the Southern Ocean under diverse spatial distributions. We use a global ocean and sea‐ice model to explore whether the spatial distribution and magnitude of meltwater fluxes can alter AABW properties and formation. We find that a realistic spatially varying meltwater flux sustains AABW with higher salinities compared to simulations with uniform meltwater fluxes. Finally, we show that increases in ice sheet melting above 12% since 1958 can trigger AABW freshening rates similar to those observed in the Southern Ocean since 1990, suggesting that the increasing Antarctic meltwater discharge can drive the observed AABW freshening.